ALIANSI GRAMATIKAL PADA BAHASA MANDARIN: TIPOLOGI BAHASA - Reja Aprilla Brahmana; Mulyadi (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
This research about the grammatical alliance system in daily newspaper texts. The data is taken from complex Mandarin sentences contained in daily newspaper texts in the form of a combination of transitive and intransitive clauses, intransitive and transitive clauses, transitive and intransitive clauses, and transitive and transitive clauses. The theory used to analyze the aspects formulated in this study is the typological theory proposed by Comrie (1988) and Artawa (2004). The results of data analysis show that the Mandarin language contained in daily newspaper texts is included in the accusative and ergative language typology and the basic alliance system of Mandarin can be in the form of S = P where, A is different, and S = A, where P is different, is accusative and ergative.